Bioactive Compounds of n-Hexane Fraction of Syzygium samarangense Stem Bark and Molecular Docking Study as Anticancer Agent - Tukiran, Tukiran; Sururi, Ahmad Misbakhus; Constanty, Irene Cornelia (Molekul, 2025)
ABSTRACT. Syzygium samarangense or jambu Semarang is one of the typical Indonesian plants whose stem bark is rarely used. Research reports on stem bark provide the potential for development in the medical field, especially in cancer. The main objectives of this study were to identify its bioactive content and describe its potential bioactivity as an EGFR inhibitor for anticancer candidates in silico. The stages of the research was started with extraction (methanol), then fractionation (n-hexane) to obtain n-hexane fraction. Then, identification of the chemical content of the fractions was carried out using LC-MS. In order to know the content of anticancer potency of the identified compounds was analyzed by molecular docking. It can be reported that there are totally 35 compounds in the fraction. Based on molecular docking analysis, There were 4 of 35 compounds in the fraction, which had anticancer potency namely: isoengeletin (i); epibetulinic acid (ii); myricitrin (iii), and stigmasterol-3-O-β-D-glucoside (iv). Through PASS prediction data, it is known that the four compounds have the potency to be antineoplastic and anticarcinogenic with moderate to high activity categories. Further studies, such as in vitro and in vivo, are needed to validate its bioactivity as an anticancer. Keywords: anticancer, bioactivity, LC-MS, molecular docking, Syzygium samarangense